Frontispiece: Deconvolving Contributions to Decoherence in Molecular Electron Spin Qubits: A Dynamic Ligand Field Approach. Issue 37 (2nd July 2021) - Mirzoyan, Ruben; Kazmierczak, Nathanael P.; Hadt, Ryan G.
Abstract : Transition metal complexes have recently gained momentum as electron spin‐based quantum bit (qubit) candidates due to their synthetic tunability and long achievable coherence times. The decoherence of magnetic quantum states imposes a limit on the use of these qubits for quantum information technologies, such as quantum computing, sensing, and communication. With rapid recent development in the field of molecular quantum information science, a variety of chemical design principles for prolonging coherence in molecular transition metal qubits have been proposed. To find out more, see the Minireview by R. G. Hadt et al. on page 9482 .